Urban Agglomerations and Employment Transitions in Ethiopia - Kamei, Akito; Nakamura, Shohei (World Bank, Washington, DC, 2020)
Agglomeration boosts economic growth. A vast literature has empirically assessed the effects of agglomeration by estimating the city population elasticity on wages. This conventional approach is not necessarily suitable for analyzing urbanization at the early stage in developing countries, where a majority of urban workers engage in self-employment and/or informal jobs. Focusing on one of the poorest and largest among those countries, this paper sheds light on an aspect of urbanization and agglomeration: the transition in the mode of labor from self-employment/informal jobs to wage employment/formal jobs. Applying the instrumental variable approach to national labor force survey data sets, the analysis underscores several labor market transitions across space in urban Ethiopia. First, the town population size and the share of workers with wage employment are strongly correlated. The probability of engaging in wage work increases by 4.5 percentage points with a log increase in population size. Second, this relationship is particularly strong among disadvantaged workers, such as the female, young, and/or less educated population. Finally, the study documents higher labor force participation and lower underemployment in larger towns.